Testosterone treatment combined with exercise to improve muscle strength, physical function and quality of life in men affected by inclusion body myositis: A randomised, double-blind, placebo-controlled, crossover trial - Sophia G. Connor; Timothy J. Fairchild; Yvonne C. Learmonth; Kelly Beer; Ian Cooper; Glenn Boardman; Shaun Y. M. Teo; Behnaz Shatahmasseb; Rui Zhang; Krystyne Hiscock; Jerome D. Coudert; Bu B. Yeap; et al. (PLoS ONE, 2023)
Introduction Inclusion body myositis (IBM) is the most commonly acquired skeletal muscle disease of older adults involving both autoimmune attack and muscle degeneration. As exercise training can improve outcomes in IBM, this study assessed whether a combination of testosterone supplementation and exercise training would improve muscle strength, physical function and quality of life in men affected by IBM, more than exercise alone. Methods This pilot study was a single site randomised, double-blind, placebo-controlled, crossover study. Testosterone (exercise and testosterone cream) and placebo (exercise and placebo cream) were each delivered for 12 weeks, with a two-week wash-out between the two periods. The primary outcome measure was improvement in quadriceps isokinetic muscle strength. Secondary outcomes included assessment of isokinetic peak flexion force, walk capacity and patient reported outcomes, and other tests, comparing results between the placebo and testosterone arms. A 12-month Open Label Extension (OLE) was offered using the same outcome measures collected at 6 and 12-months. Results 14 men completed the trial. There were no significant improvements in quadriceps extension strength or lean body mass, nor any of the secondary outcomes. Improvement in the RAND Short Form 36 patient reported outcome questionnaire ‘emotional wellbeing’ sub-category was reported during the testosterone arm compared to the placebo arm (mean difference [95% CI]: 6.0 points, [95% CI 1.7,10.3]). The OLE demonstrated relative disease stability over the 12-month period but with a higher number of testosterone-related adverse events. Conclusions Adding testosterone supplementation to exercise training did not significantly improve muscle strength or physical function over a 12-week intervention period, compared to exercise alone. However, the combination improved emotional well-being over this period, and relative stabilisation of disease was found during the 12-month OLE. A longer duration trial involving a larger group of participants is warranted.